PENGARUH LAMA PENGERINGAN TERHADAP PENERIMAAN KONSUMEN SELAI LEMBARAN BUAH Sonneratia ovata - Pratiwi Ariani; Andi Noor Asikin; Bagus Fajar Pamungkas; Ita Zuraida (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
Sonneratia ovata is a mangrove fruit that has a distinctive aroma and sour taste, making it suitable for processing into jam. Slice jam is a modified form of spreadable jam that is more practical in serving. The purpose of this study was to determine the effect of drying time on the consumer acceptance of Sonneratia ovata slice jam. The research used a Completely Randomized Design (CRD) with different drying times for slice jam (120 minutes, 150 minutes, 180 minutes and 210 minutes) and three replications. Data analysis using Kruskal-Wallis, if there is a different between the treatment continued by the Multiple Comparisons test. The results showed that the drying time had a significant effect (p<0.05) on the consumer acceptance of Sonneratia ovata slice jam. 210 minutes of drying time (P4) is the best treatment based on the hedonic test value of appearance, aroma, taste, texture and overall parameters. Panelists like the appearance of Sonneratia ovata slice jam, which has brown reddish color and compact texture, but panelists dislike the smell and the sour taste of slice jam.